Association of Genomic Domains in BRCA1 and BRCA2 with Prostate Cancer Risk and Aggressiveness - Patel, Vivek L.; Busch, Evan L.; Friebel, Tara M.; Cronin, Angel; Leslie, Goska; McGuffog, Lesley; Adlard, Julian; Agata, Simona; Agnarsson, Bjarni A.; Ahmed, Munaza; Aittomäki, Kristiina; Alducci, Elisa; et al. (Cancer research, 2019)
Pathogenic sequence variants (PSV) in BRCA1 or BRCA2 (BRCA1/2) are associated with increased risk and severity of prostate cancer (PCa). We evaluated whether PSVs in BRCA1/2 were associated with risk of overall PCa or high grade (Gleason 8+) PCa using an international sample of 65 BRCA1 and 171 BRCA2 male PSV carriers with PCa, and 3,388 BRCA1 and 2,880 BRCA2 male PSV carriers without PCa. PSVs in the 3’ region of BRCA2 (c.7914+) were significantly associated with elevated risk of PCa compared with reference bin c.1001-c.7913 (HR=1.78, 95%CI: 1.25-2.52, p=0.001), as well as elevated risk of Gleason 8+ PCa (HR=3.11, 95%CI: 1.63-5.95, p=0.001). c.756-c.1000 was also associated with elevated PCa risk (HR=2.83, 95%CI: 1.71-4.68, p=0.00004) and elevated risk of Gleason 8+ PCa (HR=4.95, 95%CI: 2.12-11.54, p=0.0002). No genotype-phenotype associations were detected for PSVs in BRCA1. These results demonstrate that specific BRCA2 PSVs may be associated with elevated risk of developing aggressive PCa.